2016
DOI: 10.1371/journal.pone.0166166
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis of Randomised Trials to Ascertain Fatal Gastrointestinal Bleeding Events Attributable to Preventive Low-Dose Aspirin: No Evidence of Increased Risk

Abstract: BackgroundAspirin has been shown to lower the incidence and the mortality of vascular disease and cancer but its wider adoption appears to be seriously impeded by concerns about gastrointestinal (GI) bleeding. Unlike heart attacks, stroke and cancer, GI bleeding is an acute event, usually followed by complete recovery. We propose therefore that a more appropriate evaluation of the risk-benefit balance would be based on fatal adverse events, rather than on the incidence of bleeding. We therefore present a liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 64 publications
(66 reference statements)
5
27
0
1
Order By: Relevance
“…A higher incidence of hospitalized UGIB was reported among low-dose aspirin users in Denmark (3.64 per 1000 person-years) using a prescription database and hospital discharge registry records with data collected from 1991 to 1995. 12 As expected by the low case fatality rates, the incidence of fatal UGIB and LGIB in our study cohort was substantially lower than the incidence of nonfatal events, in line with data from aspirin randomized controlled trials 14 and observational data from secondary prevention aspirin users. 8 The absolute rate of fatal GIBs in Elwood's meta-analysis of randomized controlled trial data was much higher at 0.37 per 1000 person-years than in our study cohort; the incidence of all GIBs was also substantially higher, at 8 cases per 1000 personyears.…”
Section: Almost Three-quarters Ofsupporting
confidence: 88%
See 2 more Smart Citations
“…A higher incidence of hospitalized UGIB was reported among low-dose aspirin users in Denmark (3.64 per 1000 person-years) using a prescription database and hospital discharge registry records with data collected from 1991 to 1995. 12 As expected by the low case fatality rates, the incidence of fatal UGIB and LGIB in our study cohort was substantially lower than the incidence of nonfatal events, in line with data from aspirin randomized controlled trials 14 and observational data from secondary prevention aspirin users. 8 The absolute rate of fatal GIBs in Elwood's meta-analysis of randomized controlled trial data was much higher at 0.37 per 1000 person-years than in our study cohort; the incidence of all GIBs was also substantially higher, at 8 cases per 1000 personyears.…”
Section: Almost Three-quarters Ofsupporting
confidence: 88%
“…Low case-fatality rates for GIBs have also been shown among individuals randomized to low-dose aspirin in clinical trials, especially among those without ischemic vascular disease. 14…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Longer use is likely to have greater benefits. The predominant adverse event caused by aspirin is GI bleeding, and there appears to be no valid evidence that the overall frequency of fatal GI bleeding is increased by daily low-dose aspirin [36,57,58]. On the other hand, recent populationbased study from the United Kingdom showed that lowdose aspirin was not associated with increased survival of patients diagnosed with esophageal or gastric cancer [59].…”
Section: Chemopreventionmentioning
confidence: 99%
“…In addition to assessing bleeding risks according to the target population (primary or secondary CVD prevention), a full evaluation of low-dose aspirin-associated GI bleeding would cover the severity of bleeds (case-fatality, need for hospitalization) and the bleed location (upper or lower GI tract)data on low-dose aspirin-associated risks of lower GI bleeding are scarce. A recent metaanalysis of data from aspirin clinical trials (where doses ranged from 75 mg to 1900 mg daily) found no significant increase in the risk of fatal GI bleeds in subjects randomized to aspirin compared with placebo [14]. Using data from a validated UK primary care database -The Health Improvement Network (THIN)we aimed to quantify the association between new use of low-dose aspirin and risk of upper and lower gastrointestinal bleeding (UGIB/LGIB), including by level of healthcare assistance received (hospitalized or referred only), case-fatality, specific GI tract location, characteristics of aspirin (dose and duration) and according to primary/secondary CVD prevention population.…”
Section: Introductionmentioning
confidence: 99%